Syphilis in pregnancy, factors associated with congenital syphilis and newborn conditions at birth - de Almeida, Anelisa Soares [UNESP]; Andrade, Juliane; Fermiano, Rosemary [UNESP]; Jamas, Milena Temer [UNESP]; Carvalhaes, Maria Antonieta de Barros Leite [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP] (FapUNIFESP (SciELO), 2021)
Objectives: to investigate factors associated with the occurrence of congenital syphilis in pregnant women with syphilis and to describe the cases of this disease regarding the justification for notification and aspects related to the newborn. Method: cohort study, with data collection between July and September 2017 which included 158 pregnant women diagnosed with syphilis during pregnancy, reported between 2013 and 2015. The characteristics of pregnant women and newborns are presented descriptively. The outcome under study was the occurrence or not of congenital syphilis. Sociodemographic exposure variables related to prenatal care and the adequacy of maternal syphilis treatment were analyzed by the stepwise selection criteria, and those that presented p<0.20, included in adjusted analysis, when critical p <0.05 was adopted. Results: most pregnant women with syphilis were white, had nine or more years of schooling and did not work. Among the participants, 74 (46.8%) had a newborn with congenital syphilis. Independently, the number of prenatal consultations was the only factor associated with congenital syphilis: as the number of consultations increased, the occurrence decreased (p=0.013, OR=0.87, 95%CI=0.79-0.97). The non-treatment of the mother and partner were the most frequent justifications for defining the case of congenital syphilis, and 33 newborns with syphilis presented complications at birth. Conclusion: considering the association with the number of prenatal consultations, in order to reduce cases of congenital syphilis, the municipality should modify the follow-up in this period, offering consultations, developing health education actions, implementing diagnostic investigation and appropriate treatment for pregnant women, and partnership when necessary.
Sífilis en el embarazo, factores asociados con la sífilis congénita y condiciones del recién nacido al nacimiento
Sífilis na gestação, fatores associados à sífilis congênita e condições do recém-nascido ao nascer
Keywords: Congenital syphilis; Longitudinal studies; Pregnancy; Risk factors; Syphilis